Factor that contributes to financial development in Malaysia / Nurul Nadia Jais - Jais, Nurul Nadia (2018)
This study was aimed to investigate the relationship between micro-factor and financial development such as economic growth and trade openness in Malaysia measured by Domestic Credit to Private Sector, GDP Growth and Trade over the 30 years (19852015). In the other hand, this studies is show how the factors will affect the financial development. The finding of this study indicates that two factors which are economic growth and trade openness has insignificant relationship with financial development. Therefore, in order to gain a deeper understanding of the factors, research is necessary.